Cold Hardiness in Trees: A Mini-Review - Wisniewski, Michael; Nassuth, Annette; Arora, Rajeev (Frontiers in Plant Science, 2018)
Significant advances have been made in our understanding of the regulation of cold hardiness. The existence of numerous biophysical and biochemical adaptive mechanisms in perennial woody plants has made the development of methods for managing and improving cold hardiness in perennial woody plants difficult. This may be partially attributed to viewing cold hardiness as a single dimensional response, rather than as a complex phenomenon, involving different mechanisms (avoidance and tolerance), different stages (mid-winter vs. late winter), and having an intimate overlap with the genetic regulation of dormancy. In particular separating the molecular regulation of cold hardiness from growth processes has been challenging. ICE and CBF transcription factors (Inducer of CBF expression and CRT-binding factor) have been shown to be an important aspect in the regulation of cold-induced gene expression. Evidence has emerged, however, that it is also intimately involved in the regulation of growth, flowering, dormancy, and stomatal development. This evidence includes the presence of CBF binding motifs in genes regulating these processes, or through cross-talk between the pathways that regulate them. Recent changes in climate that have resulted in erratic episodes of unseasonal warming followed by more seasonal patterns of low temperatures has also highlighted the need to better understand the genetic and molecular regulation of deacclimation, a topic of research that is only more recently being addressed. Environmentally-induced epigenetic regulation of stress responses and seasonal processes such as cold acclimation, deacclimation, and dormancy have been documented but are still poorly understood. Advances in the ability to efficiently generate large DNA and RNA datasets and genetic transformation technologies have greatly increased our ability to explore the regulation of gene expression and explore genetic diversity. Greater knowledge of the interplay between epigenetic and genetic regulation of cold hardiness, and the application of advanced genetic analyses, such as genome-wide-association-studies (GWAS), are needed to develop strategies for addressing the complex processes associated with cold hardiness in woody plants. A cautionary note is also indicated regarding the time-scale needed to examine and interpret plant response to freezing temperatures.